Safety, tolerability, and pharmacokinetics of a single ascending subcutaneous dose of GSK3772847 in healthy participants - Eleni Pefani; Sally Stone; Chang‐Qing Zhu; Carol Nunn; David Fairman (Wiley, 2023)
Abstract The aim of this study was to evaluate the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of GSK3772847, compared with placebo administered subcutaneously (SC) in healthy participants, including cohorts of Japanese and Chinese participants. This was a single‐center, randomized, placebo‐controlled, double‐blind, single ascending dose study. Following a screening period of up to 28 days, eligible participants were assigned to one of four cohorts receiving a single dose of GSK3772847 70 mg (cohort 1) or 140 mg (cohorts 2, 3, and 4) or placebo SC. In cohorts 1 and 2, participants were randomly assigned to one of three injection sites (upper arm, abdomen, or thigh), while cohorts 3 and 4 included Japanese and Chinese participants, respectively, assigned to receive GSK3772847 or placebo SC (upper arm). Participants attended follow‐up visits on Days 9, 15, 29, 43, 57, 71, and 85 before final analysis. GSK3772847 was generally well tolerated. Most adverse events (AEs) were mild, resolved without treatment and were considered not related to study treatment by the investigator. There were no serious AEs or deaths during the study. The PK and PD were dose dependent, with negligible differences across injection sites or ethnicities. Target engagement was demonstrated by reduced free soluble interleukin 33 (sIL‐33) concentrations and substantially increased total sIL‐33 concentrations compared with baseline. Subcutaneously administered GSK3772847 was well tolerated in healthy participants, including cohorts of Japanese and Chinese participants, and shows consistent PK and PD across injection sites and ethnicities.